Effect of Polyethylene Fiber on Fracture Resistance of Bulk-fill Composites - MANAV, AYBİKE; DOĞU, BENGÜ; YILMAZ ATALI, PINAR; KAHRAMANOĞLU, ERKUT; ŞENOL, AYŞE ASLI; TARÇIN, BİLGE; TÜRKMEN, CAFER (My University, 2023)
Introduction: The aim of this in vitro study was to evaluate the fracture resistance of sonic-activated SonicFill3 (SF) (Kerr) and flowable Charisma Bulk Flow ONE (CO) (Kulzer) bulk-fill composites with or without polyethylene-fiber (R) (Ribbond) application. Materials and Methods: Class I cavities (2x2x4mm) were prepared on 40 freshly extracted human premolars of similar size and classified randomly into 4 groups (SF, SF+R, CO, CO+R). The remaining wall thicknesses of the teeth was confirmed to be 2mm. Ribbond fiber (2x2mm) was applied to cavity bases of the acryl-embedded teeth according to manufacturers’ instructions and OptiBond (Kerr) (for SF, SF+R groups) and Gluma Bond (Kulzer) (for CO, CO+R groups) universal adhesives were used. All specimens were restored in a 4mm monolayer with SF and CO. Valo Cordless (Ultradent) LED-curing unit with a power output of 1000 mW/cm2 was preferred for polymerization. Finishing and polishing were completed with the last 2 stages of Sof-Lex discs (Kerr). Restored teeth were stored in distilled water at 37°C for 24 hours. Fracture resistance (FS) and elastic modulus (EM) values were measured with a universal testing device (Shimadzu AG-X, Shimadzu Corp, Japan). Data were analyzed with IBM SPSS V23 using Independent samples T-test. The significance level was set at p<0.05. Results: No statistically significant difference was found between the bulk-fill composites (SF and CO) without R (p=0.167). Similarly, no significant difference was detected between the Ribbond fiber applied groups (SF+R and CO+R) (p=0.994). The effect of fiber application on FS of SF (p=0.421) and CO (p=0.552) was not statistically significant. The mean maximum force values (newtons) in decreasing order were CO (761.09±224.32) > SF+R (671.08±150.51) > CO+R (669.95±358.44) > SF (580.7±269.04). The EM values of SF and CO were statistically significantly different (p=0.009). A statistically significant difference was observed between the EM values in the Ribbond fiber applied groups (SF+R and CO+R) (p=0.026). EM values of CO were statistically significantly higher regardless of Ribbond application (p<0.001). Conclusion: Within the limitations of this in vitro study, the application of SonicFill3 and Charisma Bulk Flow ONE composites with Ribbond may be an option for clinical applications. Keywords: bulk-fill composite, elastic modulus, fracture resistance, polyethylene fiber
Keywords: bulk-fill composite; elastic modulus; fracture resistance; polyethylene fiber